The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3139/217.3489
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Titanium Dioxide Modified Expandable Graphite and Ammonium Polyphosphate on Combustion Behavior and Physicomechanical Properties of Rigid Polyurethane Foam

Abstract: In this research, the individual influence and synergistic behavior between titanium dioxide modified expendable graphite and ammonium polyphosphate on combustion behavior and physicomechanical properties of rigid polyurethane foam (RPUF) were investigated. Combustion behavior was evaluated by limiting oxygen index, and vertical-combustion tests. Thermal stability was studied via thermogravimetric/differential thermal gravimetric (TG/DTG) analysis. Results showed that the modified expendable graphite presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…This is because APP can act as a nucleating agent in the foaming process (refer to Fig. b) . Due to its small particle size and high density, the APP can be embedded in the wall.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because APP can act as a nucleating agent in the foaming process (refer to Fig. b) . Due to its small particle size and high density, the APP can be embedded in the wall.…”
Section: Resultsmentioning
confidence: 99%
“…Pure RPUF was prepared by an oneshot, free rise procedure according to the reported method . Firstly, the component I was prepared from that 100 g of polyether polyol, 2.0 g of silicon oil, 0.3 g of N,N,N′,N′,N″‐pentamethyldiethylenetriamine, 1.5 g of triethylene diamine, 2.5 g of potassium acetate, 0.5 g of deionized water, 40 g of dichlorofluoroethane and a certain mass of FRs such as EG P , the reference EG 0 , APP, mixture of EG P and APP.…”
Section: Methodsmentioning
confidence: 99%
“…EG included at 10–25 wt% is among the most popular types of intumescent flame retardant used in the production of nontoxic fire‐safe polymeric foams and coatings. However, almost all previous studies have reported on the efficiency of EG in polyurethane (PU) foams and PU composites [10–12].…”
Section: Introductionmentioning
confidence: 99%